Genome-wide identification and characterization of argonaute, dicer-like, and RNA-dependent RNA polymerase gene families in potato (Solanum tuberosum): Advancing RNA interference-based crop enhancement - Md. Nahid Hasan Shuvo; Mahmudul Hassan; Md. Abu Musa; Riday Hossain; Jesmin Naher Konak; Zobaer Akond; Fee Faysal Ahmed (PLoS ONE, 2026)
In eukaryotic species, RNA silencing is a conserved mechanism for controlling gene expression. The RNA-dependent RNA polymerase (RDR), argonaute (AGO) , and dicer-like (DCL) proteins are essential for RNA silencing. The RNA interference (RNAi) system regulates eukaryotic gene expression throughout growth, development, and stress response. It is also closely linked the post-transcriptional gene silencing (PTGS) process. The potato is one of the four major food crops and a staple meal in the world that has a great potential to combat global malnutrition. However, no genome-wide analysis of the silencing gene family has yet to be conducted in the economically significant plant potato. In this study, we identified 29 (6 StDCL , 14 StAGO and 9 StRDR ) candidate genes in potato. These genes correspond to the Arabidopsis thaliana RNAi silencing genes. The analysis of the conserved domain, motif, and gene structure for StDCL , StAGO , and StRDR genes showed higher homogeneity within the same gene family. The Gene Ontology (GO) enrichment analysis exhibited that the identified RNAi genes could be involved in RNA silencing and associated metabolic pathways. A number of important transcription factors (TFs), BBR-BPC, bHLH, bZIP, C2H2, Dof, ERF, MIKC MADS, WRKY families, were identified by network and sub-network analyses between TFs and candidate RNAi gene families. Furthermore, the cis -acting regulatory elements (CREs) related to light, stress and hormone responsive functions and tissue-specific expression were identified in candidate genes. These genome wide analyses of these RNAi gene families provide valuable information related to RNA silencing which might be helpful for potato improvement in the breeding program.